2012
DOI: 10.1021/nl203906r
|View full text |Cite
|
Sign up to set email alerts
|

Graphene–Multilayer Graphene Nanocomposites as Highly Efficient Thermal Interface Materials

Abstract: We found that an optimized mixture of graphene and multilayer graphene -produced by the high-yield inexpensive liquid-phase-exfoliation technique -can lead to an extremely strong enhancement of the cross-plane thermal conductivity K of the composite. The "laser flash" measurements revealed a record-high enhancement of K by 2300 % in the graphene-based polymer at the filler loading fraction f =10 vol. %. It was determined that a relatively high concentration of single-layer and bilayer graphene flakes (~10-15%)… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

25
879
3
5

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 1,315 publications
(912 citation statements)
references
References 45 publications
(153 reference statements)
25
879
3
5
Order By: Relevance
“…Studies have reported that surfactants can mediate filler-polymer interactions and enhance the filler-tomatrix transfer properties [42,44,69,70,78], though different conclusions were reached.…”
Section: Accepted M Manuscriptmentioning
confidence: 99%
See 2 more Smart Citations
“…Studies have reported that surfactants can mediate filler-polymer interactions and enhance the filler-tomatrix transfer properties [42,44,69,70,78], though different conclusions were reached.…”
Section: Accepted M Manuscriptmentioning
confidence: 99%
“…The more efficient CNTs are also much more expensive, and the use of graphene potentially allows for comparable enhancement of physical properties at a fraction of the cost [27,78].…”
Section: Accepted M Manuscriptmentioning
confidence: 99%
See 1 more Smart Citation
“…The first one is the high interfacial thermal resistance between graphene and matrix materials 2,10 . Recent investigation showed that the interfacial thermal resistance could be overcome by alignment arrangement of graphene in composites 6 .…”
Section: Introductionmentioning
confidence: 99%
“…1 "Softness" (or the ability to deform under pressure) allows TIMs to fill in surface roughness crevices and improve the effective heat transfer between substrates; however, soft materials with high thermal conductivity are difficult to manufacture due to the low intrinsic thermal conductivity of polymers, typically between 0.1 and 0.5 W/m-K 2 (with the exception of recent efforts to increase the thermal conductivity of pure polymer, where up to 1.5 W/m-K has been achieved using engineered interchain, heat conducting bonds 3 ). To overcome this challenge, commercial TIM manufacturers and academic researchers generally fill the polymer matrix with thermally conductive particles such as boron nitride or aluminum oxide particles (for electrically insulating applications) 4,5 or various forms of carbon such as carbon fibers, 6 carbon nanotubes, 7 and graphene flakes 8 and metals including Ag 9 (for applications where electrical isolation is less critical). Although the aforementioned filler particles exhibit large thermal conductivities, the effective increase in composite thermal conductivity can be low because of poor particle dispersion and contact resistance, which includes both phonon scattering at the polymer matrix and filler particle interface and voiding or incomplete wetting of the particle surface.…”
mentioning
confidence: 99%